The Theme of Death in the Novels of Anna Mostowska and Łucja Rautenstrauchowa - Kusek, Monika (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
In the gothic novel in the late 18th and early 19th centuries scary death scenes were very common.The writers from the period usually described the scenes of death in a very naturalistic way. Some of themprobably wanted to implement Edmund Burke’s theory, according to which the fear of death is the mostintensive expression of terror. We must experience it in order to be able to know the feeling of sublimity.The subject of my thesis is the writing of Anna Mostowska and Łucja Rautenstrauchowa. The first ofthem was the one who introduced the gothic novel as a new genre at the end of the 18th century. Therehave been analyzed the scenes of death occurring in their novels. Even though they were full of irrational,fantastic elements already announcing Romanticism, yet they had their origin in the Enlightenment. Thefollowing pictures of death are connected with the tendency to moralization and didacticism. In accordancewith the rules, the good people are rewarded, and the bad ones are punished with unexpected death, that isoften caused either by the influence of supernatural forces or by the realization of a prophecy.